2021
DOI: 10.1002/kjm2.12349
|View full text |Cite
|
Sign up to set email alerts
|

Herp knockout protects against nonalcoholic fatty liver disease in mice on a high fat diet

Abstract: This study aims to discover the role of Homocysteine-induced ER protein (Herp) deficiency in high-fat diet (HFD)-induced nonalcoholic fatty liver disease (NAFLD). After 8 weeks of feeding with normal-fat diet (NFD) or HFD, WT (wild type) and Herp −/− mice were measured for the body weight, liver weight and serum biochemical parameters. HE, Oil Red O, and Sirius red stainings were used to evaluate the histopathological changes of liver tissues. QRT-PCR, Western blotting and Immunohistochemistry were employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown that HERP is implicated in diverse cellular processes including ERAD [12] , [19] , [28] , metabolic regulation [16] , Ca 2+ homeostasis [14] , cell proliferation [17] , [30] , cell apoptosis [17] , and ferroptosis [18] . However, further functions and the exact mechanisms by which HERP carries out its biological functions are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that HERP is implicated in diverse cellular processes including ERAD [12] , [19] , [28] , metabolic regulation [16] , Ca 2+ homeostasis [14] , cell proliferation [17] , [30] , cell apoptosis [17] , and ferroptosis [18] . However, further functions and the exact mechanisms by which HERP carries out its biological functions are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…HERP is strongly upregulated by the unfolded protein response, which has been closely related to the pathogenesis of Parkinson’s disease, type 2 diabetes, and neurodegeneration [13] , [14] , [15] . According to a previous report, HERP may play a role in nonalcoholic fatty liver disease (NAFLD) [16] , which indicates that HERP could influence metabolism. Emerging data suggests that HERP mediates the regulation of liver cancer cell survival, inhibiting cell apoptosis and ferroptosis by different signaling pathways [17] , [18] .…”
Section: Introductionmentioning
confidence: 98%
“…Tissues were paraffin embedded and sectioned at a thickness of 5 μ m. Masson staining and wheat germ agglutinin (WGA) staining were performed to assess cardiac fibrosis and hypertrophy, respectively, as described previously [ 6 ]. Haematoxylin-eosin (H&E) and Oil Red staining were performed to assess structural changes and lipid accumulation in the liver, respectively, as described previously [ 22 ]. The fluorescence of WGA was imaged using an inverted confocal microscope (Zeiss LSM 800).…”
Section: Methodsmentioning
confidence: 99%